PENGARUH LATAR BELAKANG PENDIDIKAN DAN PELATIHAN TERHADAP KUALITAS KEPEMIMPINAN (STUDI EMPIRIS LINGKUNGAN PEMERINTAH DAERAH KABUPATEN BENGKALIS PROVINSI RIAU) - Al-Hanif, M. Rifki; Zulfadil, Zulfadil; Rama, Rovanita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the Influence of Education Background and Employee Training in Improving the Quality of Leadership. As for the population in this study are all permanent employees in the Local Government District of Bengkalis from Pim level III and IV which amounted to 18 people for Pim level III and 52 people for Level IV Pim. Sampling is done by census method. Analysis of data used is multiple linear regression with the help of SPSS program version 18.00. the results of the tests, the simultaneous test (F-test) shows that the educational background and training of employees together affect the quality of leadership, while the partial test (T-test) shows that there is a significant influence between educational background and training employees jointly to leadership qualities in the Bengkalis District Government Environment.To maximize the quality of leadership, Bengkalis Regency Government should emphasize to the employees, especially the officials of the institution to always try to improve their knowledge by participating in personnel training held by the central government or other institutions such as training conducted by universities (Universities).Keywords : Education Background, Employee Training, Quality Of Leadership